A facile non‐vacuum‐based Cu2ZnSnSe4 superstrate solar cell with 2.44% device efficiency. Issue 5 (11th January 2016) - Zhang, Yongzheng; Sun, Yuxiu; Wang, Hao; Yan, Hui
Abstract : Cu2 ZnSnSe4 (CZTSe) solar cell with a facile superstrate structure of carbon/CZTSe/CdS/ITO was fabricated entirely by non‐vacuum processes. The influence of selenization temperature on the composition of CZTSe layer was briefly investigated. Compared with current superstrate‐type CZTS(e) solar cells, the present CZTSe superstrate solar cell exhibited a higher power conversion efficiency of 2.44%.